2019
DOI: 10.1177/1747954119861076
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the risk of athlete burnout: Psychosocial, sociocultural, and individual considerations for coaches

Abstract: Past research suggests that athletes’ relationships with their coach can act as a risk factor in the development of burnout. Coaching practice may be enhanced through understanding the multidimensional factors that can augment the associations between coach–athlete relationship quality and athlete burnout. The present study explored both individual difference characteristics (gender, age, and sport level) and sociocultural factors (sport type) as moderators of this relationship. Our findings show statistically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…This same author evidences in a study with athletes from the National Collegiate Athletic Association that athletes' negative relationships with family members predict higher levels of depression and mental health problems [20]. Whether biological or psychosocial factors, some of these variables, such as the athlete-coach relationship, can reduce burnout [21].…”
Section: Psychosocial Aspects In University Athletesmentioning
confidence: 82%
See 1 more Smart Citation
“…This same author evidences in a study with athletes from the National Collegiate Athletic Association that athletes' negative relationships with family members predict higher levels of depression and mental health problems [20]. Whether biological or psychosocial factors, some of these variables, such as the athlete-coach relationship, can reduce burnout [21].…”
Section: Psychosocial Aspects In University Athletesmentioning
confidence: 82%
“…As a result of the advent of COVID-19, home confinement has been adopted as a mandatory measure in many parts of the world, and although its main objective is to reduce contagion, it involves other health risks, such as stress, anxiety, sleep disturbances, and mood disorders [45]. Confinement as a preventive measure has benefits, but also adverse or undesirable effects in the general population, so urgent measures are suggested to mitigate the negative effects on people's mental health [21], also considering the benefits of physical activity and increased well-being and resilience [46]. In relation to university athletes, the measures have also had adverse effects, as they have limited the possibility of athletes to continue at a competitive level and to participate in tournaments, affecting the levels of physical activity, anxiety, demotivation, and in some cases burnout syndrome [21].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the levels of control and autonomy support in coaching behaviors have also been studied from a motivational perspective to predict athlete burnout through psychological needs and motivational regulations [ 4 ]. Davis et al [ 5 ] emphasized the important role social factors play in preventing athlete burnout, and Quested and Duda [ 6 ] reported that athletes are likely to experience higher levels of burnout if coaches show strict or controlling coaching behaviors or do not provide autonomy support.…”
Section: Introductionmentioning
confidence: 99%
“…There is a recent interest in burnout and its evolution over the years and its attempt to reduce its occurrence [24,25], and this study offers other perspectives of the theory. Few evidences have been shown so far that speak about the relationships between BPN satisfaction and burnout, but it is needed to use all autonomy subdimensions, taking into account that BPN frustration should be treated as a concept independent of satisfaction.…”
Section: Introductionmentioning
confidence: 97%